Handbook of research on strategic fit and design in business ecosystems - Hacioğlu, Ümit, 1979- (Advances in e-business research series., 2020)
"This book is a collection of innovative research that builds a futuristic view of evolving business ecosystems and a deeper understanding of business transformation processes in the new digital business era"--